Publication Review. Issue 1 (1st March 2017) - Dillon, Pat
Crafting Textiles in the Digital Age, Nithikul Nimkulrat, Faith Kane and Kerry Walton (eds) (2016) London and New York: Bloomsbury Academic, 240pp., ISBN-13: 9781472532046, h/bk, £85.00; ISBN: 9781474286206, p/bk, £19.99